PENGARUH RETROGRADASI DAN PERLAKUAN KELEMBABAN PANAS TERHADAP KADAR PATI RESISTEN TIPE III DALUGA - Agustina -; Didah Nur Faridah; Betty S. L. Jenie (Jurnal Teknologi dan Industri Pangan, 2016)
The giant swamp taro starch or daluga corm starch in this study was extracted from corms collected from Siau Island of North Sulawesi Province in Indonesia. Native starch daluga corm has low resistant starch content, so starch modifications method were needed to increase its resistant starch content. The effect of acid hydrolisis, debranching, autoclaving-cooling and heat moisture treatment on the changes of RS3 daluga were studied. The corrm starch was first modified with acid hydrolysis (HA) and debranching with pullulanase (D). The starch was then modified with one cycle autoclaving-cooling (HADAC1x), HADAC1x with heat moisture treatment (HADAC1x+HMT), three cycle autoclaving-cooling (HADAC3x), HADAC3x with heat moisture treatment (HADAC3x+HMT) which increased its RS3 content to 42.37, 40.47, 31.12, and 31.18% (db), respectively. The starch modification method can affect other chemical properties changes such as starch content, amylose content, and reducing sugar content.